Efficacy and Safety of Fusion Imaging in Radiofrequency Ablation of Hepatocellular Carcinoma Compared to Ultrasound: A Meta-Analysis - Jie, Tao; Guoying, Feng; Gang, Tang; Zhengrong, Shi; Maoping, Li (Frontiers in Surgery, 2021)
Abstract: Background: Radiofrequency ablation (RFA), generally performed under real-time guidance of ultrasound which is safe and effective, is a common minimally invasive therapy for treating hepatocellular carcinoma. Fusion imaging (FI) is a newly developed imaging method, which integrates CT/MRI accurate imaging and matches the characteristics of real-time ultrasound imaging, thereby providing a new approach to guide tumor ablation therapy. However, the efficacy and safety of fusion imaging as opposed to ultrasound in tumor ablation remains unclear. Objective: The present study sought to evaluate the difference of the efficacy and safety between fusion imaging and ultrasound in radiofrequency surgery for treatment of hepatocellular carcinoma, through a meta-analysis. Materials and Methods: Searching the stduies comparing efficacy and safety of fusion imaging and ultrasound in radiofrequency of hepatocellular carcinoma in PubMed, Embase and Cochrane Library databases, for articles published until April 2021. Random or fixed effect models were used for statistical analysis. Meta-analysis and sensitivity analysis were used on the included studies. Results: A total of six studies met predefined inclusion criteria, and were finally included in the analysis. Sensitivity and subgroup analyses, based on predetermined patient characteristics allowed minimization of bias. Fusion imaging was not significantly different from ultrasound in terms of technical efficiency, 1-,2-, and 3- years local tumor progression(LTP), complications, as well as 2-year overall survival(OS). Subgroup analysis, based on tumor mean diameter, showed that fusion imaging reduced the rate of 1- and 2-year local tumor progression in patients with tumors of mean diameter ≥15 mm comparing to ultrasound. Moreover, operative complications could be reduced in patients with tumor mean diameter ＜15 mm using fusion imaging, comparing to ultrasound. Conclusion: Overall, these results showed that fusion imaging may have little effect on improving efficacy and safety of thermal ablation in HCC patients, relative to ultrasound. However, it is a more effective method for managing large lesions, as well as those that are difficult to ablate. Further large-scale and well-designed randomized controlled trials are needed to validate these findings. Keywords: Curative effect; fusion imaging; meta-analysis; Security; Ultrasound